Estimating Long-Term Care Costs among Thai Elderly: A Phichit Province Case Study - Pattaraporn Khongboon; Sathirakorn Pongpanich (Journal of Aging Research)
Background. Rural-urban inequality in long-term care (LTC) services has been increasing alongside rapid socioeconomic development. This study estimates the average spending on LTC services and identifies the factors that influence the use and cost of LTC for the elderly living in urban and rural areas of Thailand. Methods. The sample comprised 837 elderly aged 60 years drawn from rural and urban areas in Phichit Province. Costs were assessed over a 1-month period. Direct costs of caregiving and indirect costs (opportunity cost method) were analyzed. Binary logistic regression was performed to determine which factors affected LTC costs. Results. The total annual LTC spending for rural and urban residents was on average USD 7,285 and USD 7,280.6, respectively. Formal care and informal care comprise the largest share of payments. There was a significant association between rural residents and costs for informal care, day/night care, and home renovation. Conclusions. Even though total LTC expenditures do not seem to vary significantly across rural and urban areas, the fundamental differences between areas need to be recognized. Reorganizing country delivery systems and finding a balance between formal and informal care are alternative solutions.